PHENOTYPIC DETECTION AND ANTIMICROBIAL SUSCEPTIBILITY PROFILE OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING Escherichia coli FROM SUSPECTED CASES OF URINARY TRACT INFECTION IN KANO METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Urinary tract infections (UTIs) caused by antimicrobial-resistant bacteria, especially ESBL-producing Escherichia coli can be life-threatening as therapeutic options available to treat infected patients are limited. Resistance due to ESBL-producing bacteria poses a peculiar challenge in treating infections because of its association with multidrug resistance. The aim of this study was thus to determine the susceptibility pattern and phenotypic detection of ESBL-producing E. coli from UTI patients. Two hundred and forty-six (246) E.coli isolates obtained from patients with suspected urinary tract infections were studied. The identity of the isolates was confirmed using standard biochemical tests. Antibiotic susceptibility testing was carried out using the Kirby-Bauer Disc Diffusion Technique. Screening for ESBL production was done using the Clinical Laboratory Standards Institute breakpoint. Suspected ESBL producers were subjected to confirmation using the Double Disc Synergy Test. Standard Discs of Augmentin (AMC 30µG Oxoid England), Ceftazidime (CAZ 30µG, Oxoid England) and Cefotaxime (CTX 30µG, Oxoid England) were used for the screening and confirmation. Multidrug-resistant E.coli were found to be 65.4%. Screening for ESBL production showed 67.1% suspected ESBLs producing E.coli. The Double Disc Synergy Test showed 22.4% confirmed ESBLs producing E.coli. Antimicrobial sensitivity of the ESBLs producing organisms showed 100% resistance to augmentin, ceftriaxone, ceftazidime, ciprofloxacin and cefotaxime while resistance to gentamicin was 91.1%, chloramphenicol 89.2%, nitrofurantoin 78.4%, and cotrimoxazole 94.6%. A 100% sensitivity to imipenem was also observed. ESBL-producing E.coli are present in Kano metropolis and are resistant to commonly prescribed antibiotics. We, therefore, suggest screening and confirmation for ESBL, to prevent treatment failure.
Keywords: UTI; Escherichia coli; Extended-spectrum beta-lactamase; 3rd Generation Cephalosporins; Antimicrobial susceptibility; Imipenem